Manajemen Waktu Belajar Mahasiswa Selama Pembelajaran Jarak Jauh - Bunayah, Bunayah (JOEAI (Journal of Education and Instruction), 2022)
ABSTRACT This study aims to determine student learning time management during distance learning. This research method is a qualitative descriptive research with a case study approach. Primary data collection using structured interviews and distributing questionnaires using google form. The interview technique is structured interview in which the interview questions have been pre-designed and the interview questions for all respondents are the same. The respondents were 5 Arabic Literature students at state universities which were selected and determined using purposive sampling method. The questionnaire was conducted by distributing google forms, as many as 15 students responded. Respondents were taken using a non-probability sample. The results of the study found that student respondents who have not managed study time: study only if they want to take an exam, study when there is material that is not understood, study independently according to their mood. Student respondents who manage study time: study independently of the most difficult courses, take advantage of free time by reviewing courses one by one, do assignments every night, study in the morning. When managing study time, student respondents understand the lesson to the fullest, feel more productive, disciplined, and calm, more prepared in terms of material and mental when attending class. Positive things: learning is more flexible, free time is more, preparation for class is not too time consuming and complicated, easy to learn. Negative things: constrained by the internet, delivery of material is not understandable, sometimes likes to skip lecture or lesson information. The conclusion of this research is that during distance learning students can manage study time but there are still students who have not managed their study time and distance learning has a positive and negative impact on students. Keywords: Study time manajement, distance learning